The Correlation between Self-Motivation and Self-Efficacy in Reading Comprehension of the Eighth Graders of MTS Hidayatul Mubtadiin - Balak in Academic Year 2025/2026 - Vio Ardiyanto; Nur Hasibin; Intan Minanti; Winda Creasty (LUNAR, 2026)
This study investigates the correlation between self-motivation, self-efficacy, and reading comprehension ability of eighth-grade students at MTs Hidayatul Mubtadiin – Balak in the 2025/2026 academic year. Using a quantitative correlational design, data were obtained through questionnaires on self-motivation and self-efficacy based on Guthrie & Wigfield and Bandura’s theories, along with a reading comprehension test on narrative texts guided by Snow’s framework. The results revealed that most students demonstrated high self-motivation and self-efficacy, with 71.43% categorized in the high group and none in the low group. However, their reading comprehension performance was relatively weak, as 71.43% of students were in the poor to very poor category, with an average score of 34.52 out of 100. Statistical analysis using multiple linear regression indicated a moderate positive correlation (R = 0.437) between self-motivation, self-efficacy, and reading comprehension, yet the relationship was not statistically significant (p = 0.149 > 0.05). These findings suggest that while motivation and efficacy may contribute to reading ability, they are insufficient alone to drive significant improvement. Therefore, a more comprehensive approach is required, incorporating effective reading strategies, supportive instruction, and conducive learning environments to enhance students’ reading comprehension.